IL28B gene polymorphisms in mono- and HIV-coinfected chronic hepatitis C patients - Bertol, Bruna C.; Moreira, Simone; Garcia, Raquel F. L.; Ferreira, Leslie E.; Debortoli, Guilherme; Pinho, Mauro de Souza Leite; Amendola-Pires, Marcia; Maciel, Alessandra M. de Almeida; Brandço-Mello, Carlos E.; França, Paulo H. C. de (Frontiers in Microbiology, 2015)
Introduction: Single-nucleotide polymorphisms (SNPs) associated with hepatitis C virus (HCV) clearance were identified near the IL28B gene. Coinfection by the human immunodeficiency virus (HIV) influences the course of HCV contributing to liver damage. Nevertheless, little is known about the relationship between these SNPs and HCV/HIV coinfection. Our aim was to estimate the relevance of the allelic and genotypic variants of the IL28B polymorphisms rs12979860 (C/T) and rs8099917 (T/G) on the establishment of HCV infection in HCV mono-infected and HCV/HIV coinfected patients. Methodology: A total of 199 non-infected controls and 230 patients with chronic hepatitis C, including 53 coinfected with HIV, participated in the study. Genotyping consisted of Polymerase Chain Reaction (PCR) and subsequent analysis of the restriction patterns resulting from exposure to endonucleases. Results: Among the controls with established results, 47.4% (90/190) exhibited the rs12979860 CC genotype, 43.7% CT, and 8.9% TT, whereas 29.1% (66/227), 51.5%, and 19.4% of the patients exhibited the CC, CT, and TT genotypes, respectively. With respect to rs8099917, 66.8% (133/199) of the controls exhibited the TT genotype, 31.2% TG, and 2.0% GG, whereas 56.1% (129/230), 40.9%, and 3.0% of the patients exhibited the TT, TG, and GG genotypes, respectively. Conclusions: The frequencies of the rs12979860 C allele and CC genotype and of the rs8099917 T allele and TT genotype were significantly higher among controls compared with patients, thus confirming the suggested protective effect against HCV infection. No significant difference was observed in the genotype and allelic distributions between the mono- and coinfected patients.